Organizational Commitment as a Predictor of Employee Performance in the Shrimp Processing Industry: Komitmen Organisasi Sebagai Prediktor Kinerja Karyawan di Industri Pengolahan Udang - Pradana, Afrillian Ilham; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2025)
General Background Effective Human Resources Management is crucial for organizational success and competitiveness, with employee performance being a core outcome. Specific Background Performance is often linked to organizational culture, work environment, and organizational commitment. Knowledge Gap Although these relationships are theoretically established, the specific hierarchy and magnitude of their effects in a high-production, target-oriented environment, such as the shrimp processing industry, requires empirical validation. Aims This study examines the relationship between organizational culture, work environment, organizational commitment, and employee performance at PT Panca Mitra Multiperdana Tbk Situbondo. Results Utilizing a quantitative method with a simple random sample of 86 employees, the results show that Organizational Culture and Work Environment have no significant relationship with employee performance. In contrast, Organizational Commitment is proven to be a major determinant of employee performance. Novelty This study specifies the dominance of organizational commitment over culture and physical environment in driving performance within the context of the surveyed firm. Implications The findings suggest that management should prioritize programs that bolster employee commitment to further sustain and improve overall productivity. Highlights Organizational commitment is the strongest performance predictor. Culture and work environment show no significant link to performance. Study conducted on 86 employees of PT Panca Mitra Multiperdana Tbk. Keywords: Organizational Culture, Work Environment, Organizational Commitment, Employee Performance, Shrimp Industry